Основные тенденции изменения этнического состава и структуры населения Брестской области по материалам переписей населения 1959–2009 гг. - Заруцкий, С. А.; Zarutski, S. A. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
В статье рассматриваются основные тенденции изменения этнического состава и структуры населения Брестской области по материалам переписей населения за период 1959–2009 гг. Определены условия и факторы трансформации этнической структуры населения. The article discusses the main trends affecting the ethnic composition and structure of the population of the Brest region based on population censuses for the period 1959–2009. The conditions and factors of transformation of the ethnic structure of the population are defined by the author.
Main Trends in the Ethnic Composition and Structure of the Population of the Brest Region Based on Population Censuses for the Period 1959–2009
Keywords: приграничный регион; этногеография; этнический состав и структура населения; border region; ethnogeography; ethnic composition and structure of the population